Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1111/1469-7610.00105
|View full text |Cite
|
Sign up to set email alerts
|

Stress and psychopathology in children and adolescents: is there evidence of specificity?

Abstract: Research on the relations between specific stressors and specific psychological outcomes among children and adolescents is reviewed. Specificity, the notion that particular risk factors are uniquely related to particular outcomes is discussed from a theoretical perspective, and models of specificity are described. Several domains of stressors are examined from a specificity framework (e.g., exposure to violence, abuse, and divorce/marital conflict) in relation to broad-band outcomes of internalizing and extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
188
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(205 citation statements)
references
References 170 publications
(205 reference statements)
13
188
0
4
Order By: Relevance
“…Specificity hypotheses posit life events involving separation with internalizing symptoms and life events involving conflict with externalizing symptoms [26]. As shown in the Tables 3 and 5 only two out of 17 life events and two out of six family-change-factors were associated with significantly increased CBCL scores.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Specificity hypotheses posit life events involving separation with internalizing symptoms and life events involving conflict with externalizing symptoms [26]. As shown in the Tables 3 and 5 only two out of 17 life events and two out of six family-change-factors were associated with significantly increased CBCL scores.…”
Section: Discussionmentioning
confidence: 95%
“…Studies of stressful life events as risk factor for child mental health have often focussed on the specificity of either the stressor or the outcome [18,26]. The most complex model, the stressor-outcome specific model, simultaneously tests the hypotheses that particular stressful events predict particular psychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lack of specificity between stressors and psychopathological outcomes (McMahon et al, 2003), one may hypothesize that gene-stressor interactions account for outcome specificity. Therefore, psychopathological constructs reflecting gene-environment interactions might be among the most specific and most useful endophenotypes for major depression.…”
Section: Increased Stress Sensitivity (Gender Specific)mentioning
confidence: 99%
“…Consistent with this notion, prospective research has found that a negative attributional style interacts with stressors to predict future increases in depressive symptoms and disorder among youth (e.g., Abela 2001;Dixon and Ahrens 1992;Lewinsohn et al 2001;Hilsman and Garber 1995;Robinson et al 1995;see Lakdawalla et al 2007, for a review). Negative events are broadly associated with anxiety, depression, and externalizing problems (McMahon et al 2003). …”
Section: Hopelessness Theory Of Depressionmentioning
confidence: 99%